L-glucitol oxidizing dehydrogenase from Bradyrhizobium japonicum USDA 110 for production of D-sorbose with enzymatic or electrochemical cofactor regeneration - Gauer, Sabrina; Wang, Zhijie; Otten, Harm; Etienne, Mathieu; Bjerrum, Morten Jannik; Lo Leggio, Leila; Walcarius, Alain; Giffhorn, Friedrich; Kohring, Gert-Wieland (Applied microbiology and biotechnology, 2014)
A gene in Bradyrhizobium japonicum USDA 110, annotated as a ribitol dehydrogenase (RDH), had 87 % sequence identity (97 % positives) to the N-terminal 31 amino acids of an L-glucitol dehydrogenase from Stenotrophomonas maltophilia DSMZ 14322. The 729-bp long RDH gene coded for a protein consisting of 242 amino acids with a molecular mass of 26.1 kDa. The heterologously expressed protein not only exhibited the main enantio selective activity with D-glucitol oxidation to D-fructose but also converted L-glucitol to D-sorbose with enzymatic cofactor regeneration and a yield of 90 %. The temperature stability and the apparent K ₘ value for L-glucitol oxidation let the enzyme appear as a promising subject for further improvement by enzyme evolution. We propose to rename the enzyme from the annotated RDH gene (locus tag bll6662) from B. japonicum USDA as a D-sorbitol dehydrogenase (EC 1.1.1.14).